Positive Politeness Strategies by Palpatine in Star Wars : Revenge of the Sith - Albert Yohan Firlandi; I Komang Sumaryana Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
Revenge of the Sith, highlighting how these linguistic tools function as instruments of persuasion and manipulation. As the primary antagonist who masterminds the political and military conflict, Palpatine demonstrates an exceptional ability to control and influence other characters through carefully crafted dialogues. His language choices are not merely designed to maintain social harmony or reduce face-threatening acts (FTAs), but also to achieve hidden personal objectives. By building a sense of camaraderie and shared goals, Palpatine subtly manipulates the hearer’s emotions and decisions, often leading them toward outcomes that favor his agenda. The study employs a qualitative research method, with data drawn from Palpatine’s utterances throughout the film. Brown and Levinson’s (1987) theory of politeness serves as the primary analytical framework to identify the strategies Palpatine employs. The findings indicate that Palpatine frequently uses positive politeness strategies such as offering praise, emphasizing shared values, and creating misleading “common ground” to establish trust. He also makes promises or assurances that appeal to the hearer’s desires, while concealing his manipulative intentions. This research contributes to the broader field of pragmatics and discourse analysis by demonstrating how politeness theory can be applied to fictional narratives, particularly in examining power dynamics and manipulation. Furthermore, the study illustrates how language, when strategically used, can blur the lines between genuine politeness and calculated persuasion. The results highlight the importance of critical awareness in interpreting linguistic strategies in various communication contexts, both fictional and real-world.